STYLISTIC ANALYSIS OF EARLE BIRNEY’S THE BEAR ON THE DELHI ROAD - Nurhadi, Muizzu; Marsih, Linusia (Universitas 17 Agustus 1945 Surabaya, 2022)
examine poetic expression, point of view, meaning, and themes. By using the linguistics approach, stylistics helps to objectively disclose literal meaning and poetic expression in the text. Thus, this research attempts a stylistic analysis of Earle Birney’s poem The Bear on the Delhi Road and examines how language features affect the poetic expression and literal meaning in the poem. Furthermore, this research is a content analysis approach that is analyzed through the stylistics analysis. Stylistics analysis in this research focuses on the three language levels, phonology and syntactic. In the part of phonology levels, the researchers focus on the alliteration, assonance, and consonance. While syntactic levels focus on the transitivity patterns, affixes, and pronouns. By showing how specific linguistic features contribute to the overall meaning and emotional impact of a poem, this study encourages readers and scholars alike to engage more deeply with poetic texts. It also underlines the value of stylistics in bridging the gap between linguistic theory and literary appreciation, helping to bring about a greater awareness of the complicated relationship between form and content in literature.